Are U.S. Commercial Banks Too Big? (2013)
This paper presents new nonparametric measures of scale economies and TFP growth for U.S. banks. Unlike previous studies that use fully nonparametric models, our approach controls for time-invariant unobserved heterogeneity among banks in estimating returns to scale, TFP growth and its components. Using data for U.S. commercial banks from 2001 to 2010, we find evidence of significant scale economies across the entire bank size distribution. Returns to scale are persistent over time, decrease with bank size, and contribute significantly to TFP growth. Our results indicate that almost all small and medium size banks and most of the largest banks have strong economic incentives to keep growing. Thus, the consolidation of the banking industry is unlikely to retrench in the near future.